Magnetic, Microplate-Format Plasmid Isolation Protocol for High-Yield, Sequencing-Grade DNA. (October 2000) - Skowronski, E.W.; Armstrong, N.; Andersen, G.; Macht, M.; McCready, P.M.
We have developed a rapid, microplateformat plasmid isolation procedure to purify sequencing-grade DNA templates for high-throughput DNA sequencing operations. A modified lysozyme/boiling method is used to produce a plasmid-containing supernatant that is then purified by iron bead capture. After binding, the beads are pelleted in a magnetic field, washed and the DNA eluted in water. The method yields up to 10 µg plasmid DNA from a 1-mL overnight culture in a deep-well microplate. The procedure is suitable for large-scale experiments, amenable to automation and does not require expensive reagents or equipment. The entire protocol can be completed in as little as 2 h, and one technician with a 96-well pipetting station can process up to 48 plates per day. This protocol is ideal for any highthroughput operation in which template quantity, quality and reproducibility are of primary importance.